Evaluation and analysis of the impact of seamless nursing on angina control, disease prognosis, and nursing quality in older adult patients with coronary heart disease - Wei, Fugui; Wang, Yali; Han, Wei (Frontiers in Cardiovascular Medicine, 2025)
ObjectiveTo investigate the impact of seamless nursing on angina control, disease prognosis, and nursing quality in older adult patients with coronary heart disease (CHD).MethodsA total of 100 CHD patients who were hospitalized in the cardiology department of our hospital from February 2024 to January 2025 were randomly divided into a control group (50 patients) and a study group (50 patients) using a random number table. The control group received conventional nursing care, while the study group received seamless nursing care. The Seattle Angina Questionnaire (SAQ) scores, incidence of adverse events, and nursing quality scores of both groups were observed and compared.ResultsThe SAQ scores of the study group were significantly higher than those of the control group, with improvements in physical activity limitations, angina frequency, and angina stability (P < 0.05). The incidence of adverse events in the study group was significantly lower than that in the control group (P < 0.05). The nursing quality scores for service capability, operational norms, humanistic care, and health education in the study group were significantly higher than those in the control group, with a higher total score (P < 0.05).ConclusionSeamless nursing can effectively reduce the frequency of angina, alleviate physical activity limitations, decrease the incidence of adverse events, and improve patients’ quality of life in older adult patients with coronary heart disease. It also appears to improves nursing workflows and enhances nursing quality, suggesting potential value for further clinical exploration in larger studies.